Experimental investigation of exhaust temperature effect on TEG cells power generation and assessment of engine SFC and emissions - Eid Mohamed (Engineering and Technology Journal)
The thermoelectric cell generators (TECG) convert thermal power into electrical power generated. The main factor in its operation is the temperature difference (TD) between its surfaces. An experimental investigation was conducted into the waste heat recovery performance of the TECG system. Forty thermoelectric cells (TECs) are supported on the (4 5) upper and (4 5) lower and upper arrangement of the engine exhaust manifold. The electrical power generated (EPG), exhaust gas flow rate, exhaust temperature, brake-specific fuel consumption (BSFC), and exhaust emissions were experimentally investigated under different engine speeds and 50 N.m and 100 N.m engine load conditions. Comparative results of the BSFC and emissions have ben measured with and without the TECG system. Experimental results observed that the maximum power values generated are approximately 218.5 W by TECG. An engine BSFC has been reduced by (2.56%:2.89%) under the TECG. The results show the improvement of CO is approximately 1.92% and 5.12% with the TECG system at loads 50 N.m and 100 N.m, respectively, and CO2 emission improvement by 4.32% and 4.52% with the TECG system throughout the speed range and two engine loads. The proposed TECG system, supported by a gasoline engine, is effective under high engine speed and load.